2007
DOI: 10.1091/mbc.e07-01-0070
|View full text |Cite|
|
Sign up to set email alerts
|

Small Interfering RNA-mediated Silencing Induces Target-dependent Assembly of GW/P Bodies

Abstract: Gene silencing using small interfering RNA (siRNA) is a valuable laboratory tool and a promising approach to therapeutics for a variety of human diseases. Recently, RNA interference (RNAi) has been linked to cytoplasmic GW bodies (GWB). However, the correlation between RNAi and the formation of GWB, also known as mammalian processing bodies, remains unclear. In this report, we show that transfection of functional siRNA induced larger and greater numbers of GWB. This siRNA-induced increase of GWB depended on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 50 publications
10
45
0
Order By: Relevance
“…We confirmed the level of Ago2 protein knockdown at 90% by measuring knockdown on an eGFP reporter (data not shown). It has been reported previously that Ago2 knockdown has no noticeable effect on P-body integrity or number in mammalian cells, whereas knockdown of GW182 and RCK/p54 leads to the disappearance of P-bodies, and our observations confirmed the same ( Figure 3B) (Lian et al, 2007). We then transfected Cy3-siPPIB into these cells and observed the localization pattern of siRNAs.…”
Section: Ago2 Is Required For Localization And/or Retention Of Sirnassupporting
confidence: 90%
See 4 more Smart Citations
“…We confirmed the level of Ago2 protein knockdown at 90% by measuring knockdown on an eGFP reporter (data not shown). It has been reported previously that Ago2 knockdown has no noticeable effect on P-body integrity or number in mammalian cells, whereas knockdown of GW182 and RCK/p54 leads to the disappearance of P-bodies, and our observations confirmed the same ( Figure 3B) (Lian et al, 2007). We then transfected Cy3-siPPIB into these cells and observed the localization pattern of siRNAs.…”
Section: Ago2 Is Required For Localization And/or Retention Of Sirnassupporting
confidence: 90%
“…We knocked down Ago2, GW182, and RCK/p54 in HeLa cells by using siRNA transfection (Chu and Rana, 2006;Lian et al, 2007), and we found high levels of knockdown in all cases (Ͼ80%) ( Figure 3A). We confirmed the level of Ago2 protein knockdown at 90% by measuring knockdown on an eGFP reporter (data not shown).…”
Section: Ago2 Is Required For Localization And/or Retention Of Sirnasmentioning
confidence: 96%
See 3 more Smart Citations